Pembuatan Alat Peraga Matematika untuk Meningkatkan Kreativitas Mahasiswa - Napfiah, Siti (Jurnal Tadris Matematika, 2019)
This research aim to improve the creativity the college student in mathematics learning by making mathematics display tool especially display tool from utilize secondhand. One of the way is utilize secondhand as thing which good for education, namely mathematics display tool. This research held in Telaah Matematika SD learning in IKIP Budi Utomo Malang. Subject of this research is the college student in study program of Mathematics Education. This observational type is classroom action research. The aim of this research is describe college student creativity step-up in utilize second as display tool. The success criteria of this research is the creativity value every the college student reach more than 70. Based on the observational gotten that the creativity value of the student college in pre research reach 30,  then in one cycle there the valuae of the college student is 55, and in two cycle all of the college students reach the value more than 70. Therefore this research can increase to creativity of the college student.